Historical natural disturbances shape spruce primary forest structure and indirectly influence bird assemblage composition - Kameniar, Ondrej; Baláž, Michal; Svitok, Marek; Reif, Jiří; Mikoláš, Martin; Pettit, Joseph L.; Keeton, William S.; Pettit, Jessika M.; Vostarek, Ondřej; Langbehn, Thomas; Trotsiuk, Volodymyr; Morelli, Federico; et al. (Forest ecology and management, 2021)
•First study in primary forest linking ≥250 yr. disturbance history to bird assemblage.•Bird assemblage composition was driven by disturbance related structure.•Disturbance induced forest change did not decrease bird diversity or abundance. Understanding the processes shaping the composition of assemblages in response to disturbance events is crucial for preventing ongoing biodiversity loss in forest ecosystems. However, studies of forest biodiversity responses to disturbance typically analyze immediate or short-term impacts only, while studies relating long-term disturbance history to biodiversity assemblage dynamics are rare. To address this important knowledge gap, we used a dendroecological approach to link natural disturbance history of 250 years (1750–2000) to structural habitat elements and, in turn, to breeding bird assemblages. We used data collected in 2017 and 2018 from 58 permanent study plots within 10 primary spruce forest stands distributed across the Western Carpathian Mountains of Europe. This dataset contained breeding bird counts and environmental variables describing forest density, tree diameter distribution, tree height, tree microhabitats, deadwood quantity and quality, and regeneration. Bird assemblages were significantly influenced by forest structure which was in turn shaped by disturbance dynamics (disturbance frequency, time since the last disturbance and its severity). Early successional species associated with more open habitats were positively influenced by disturbance-related structure (i.e. deadwood-related variables, canopy cover), while some species responded negatively. At the same time, overall abundance, species richness and Shannon diversity of the bird assemblage remained unchanged under variable disturbance histories. Our results support a view of primary spruce forests as a highly dynamic ecosystem, harbouring populations of bird species at all stages of succession despite significant structural changes and shifting patch mosaics over time due to natural disturbances.